EDUCATIONAL EXPERIENCES: PSYCHOMOTRICITY - Jardim, Raquel; Guidotti, Viviane (Revista Gênero e Interdisciplinaridade, 2022)
Psychomotricity is a science whose objective is the study of man in motion, whose movement, intellect and affection go together. It is through corporeity that our subjectivity is formed, because body and mind are not separated. However, what we perceive in many school environments is that the time devoted to the body is limited only to recess, emphasizing intellectual activity to the detriment of motor activity. We found that for a good learning the child has to experience joyful and pleasurable experiences. When we talk about learning, psychomotricity and playfulness, we understand that they are inseparable. Psychomotricity has the function of stimulating cognition, affectivity and language, it helps the child to master knowledge and psychomotor skills both broad and fine, as it works on motor coordination so important to the child’s development. According to Marinho et al, (2012) “The ludic has great educational value and can be used at school as one of the didactic resources in the teaching-learning process, contributing to the development of didactic-pedagogical activities”.